STUDI EXPERIMENTAL FATIK KOROSI ALUMINIUM PADUAN 7075-T6 PADA LINGKUNGAN 3,5% NaCl DENGAN INHIBITOR Na2CrO4 - Priyani Budiyarti Budiyarti (Program Studi Teknik Mesin Universitas Tarumanagara, 2018)
AA7075-T6 aluminum alloy is a material that widely used in the aircraft industry because aluminum as a lightweight metal, good machinability, good corrosion resistance and good castability and non-magnetic metals. Aluminum also has high tenacity, is easy to form and is easy to connect. Aluminum has good resistance to corrosion, however aluminum has effect to corrosion if it is on corrosive environment including AA7075-T6 aluminum alloy which used in the aircraft industry. Inhibitor is used to control a corrosion. The aims of these researchs were to investigate the effect of inhibitors on corrosion rates and the rate of fatigue crack corrosion propagation on AA7075-T6 aluminum alloys. This research is used Na2CrO4 inhibitors with variety of concentrations of 0.1%, 0.3%, 0.5% and 0.7% added to 3.5% NaCl solution. Corrosion rate test is used a method of potential dynamic polarization. Corrosion fatigue testing is carried out with constant amplitude at a frequency of 10 Hz and a voltage ratio (R) 0.1. Specimens were used cracked specimen centers (CCT) on orientation in the direction of rolling. The supporting data of the research were the mechanical properties of the material included optical microstructure observation, tensile testing and hardness testing. The results have shown that the optimal concentration of Na2CrO4 inhibitors was achieved at 0.5% which was characterized by a decreasing in corrosion rate and slower corrosion rate of fatigue cracking.